The Role Of OCCRP’s Soft Power In Framing President Joko Widodo Leadership On Corruption - Diqi Hadiq; Imam Mahdi (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This research analyzes how the Organized Crime and Corruption Reporting Project (OCCRP), as a transnational actor, frames President Joko Widodo on the issue of corruption and its impact on domestic and international public perception. This research uses a qualitative approach with soft power analysis, framing theory, and boomerang pattern, examining transnational media strategies in constructing corruption narratives. The research results show that OCCRP uses soft power through investigations and voting to nominate Jokowi as a finalist for